Indonesia economic growth determinants: Generalized method of moments (Gmm) model approachment - Aliasuddin, Noviana Yusuf, Raja Masbar (Opción, 2019)
This study aimed to analyze the determinants of economic growth in Indonesia by using time series data from the 1986-2017 and Generalized Method of Moments (GMM) model as a method. The results showed that government spending has a positive and significant effect on economic growth. However, employment and education have a negative and significant effect on economic growth. In conclusion, the government must improve the education in order to increase labor productivity, hence optimal economic growth can be achieved